2017
DOI: 10.1007/s40265-017-0832-z
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Food–Drug Interactions on Oral Drug Absorption

Abstract: Food effect, also known as food-drug interactions, is a common phenomenon associated with orally administered medications and can be defined as changes in absorption rate or absorption extent. The mechanisms of food effect and their consequences can involve multiple factors, including human post-prandial physiology, properties of the drug, and how the drug is administered. Therefore, it is essential to have a thorough understanding of these mechanisms when recommending whether a specific drug should be taken w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
144
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(150 citation statements)
references
References 188 publications
2
144
0
4
Order By: Relevance
“…Reports on the pharmacokinetics of MPH comparing fed and fasting conditions are scarce and reveal contradictory results [31,32]. Although food intake tends to increase luminal pH of the gut [33], not enough information is available regarding the pH levels in the small intestine in fed or fasting conditions and how this could affect the bioavailability of MPH.…”
Section: Discussionmentioning
confidence: 99%
“…Reports on the pharmacokinetics of MPH comparing fed and fasting conditions are scarce and reveal contradictory results [31,32]. Although food intake tends to increase luminal pH of the gut [33], not enough information is available regarding the pH levels in the small intestine in fed or fasting conditions and how this could affect the bioavailability of MPH.…”
Section: Discussionmentioning
confidence: 99%
“…These studies have suggested that dose adjustment may be required in a fasted or fed condition as well as for change of gender. 19 Several clinical trials also found that the plasma concentrations of other statins are lower in the fed state; however, no effect on overall LDL-C lowering was observed. Therefore, we investigated the effect of food and gender on rosuvastatin pharmacokinetics in healthy All values are expressed as mean ± SD except t max values, which are median (range).…”
Section: Discussionmentioning
confidence: 99%
“…18 Many drugs have demonstrated statistically significant food effects, but only a few have significant clinical relevance. 19 Several clinical trials also found that the plasma concentrations of other statins are lower in the fed state; however, no effect on overall LDL-C lowering was observed. 20,21 The main action site of statins is in the liver; therefore, the high liver uptake is important for a lipid-lowering effect.…”
Section: Discussionmentioning
confidence: 99%
“…16 Food effects can be a complex aspect of drug development. 16 Food effects can be a complex aspect of drug development.…”
Section: Discussionmentioning
confidence: 99%
“…Food-drug interactions or differences in absorption of a drug when administered with and without food are a common occurrence with many orally administered medications. 16 Food effects can be a complex aspect of drug development. Exposure to several oral tyrosine kinase inhibitors is affected by the presence of food, necessitating guidance regarding whether to dose these medications with or without food.…”
Section: Discussionmentioning
confidence: 99%